Commonly available Sabah medicinal plants used for traditional hypertension treatment - Fadzilah Awang-Kanak (Pusat e-pembelajaran, UMS, 2022)
Plant resources have been used as traditional medicine by various ethnic communities in Sabah for ages. Local people have their traditional practices and administration of local plants as medicine or alternative remedies for ailments. This work is an attempt to record the commonly available medicinal plants with the potential for anti-hypertension benefits. There are 20 species of plants that have been used by the local people in Sabah for traditional hypertension treatment. The ethnics included in this summary are, Bajau (Sama), Kadazan, Dusun, Murut (Nabawan/Pensiangan), Rungus, Sungai, Kedayan, Jawa, and Irranun (Kudat). The most cited plants that have been used as traditional remedies to lower blood pressure are Carica papaya and Orthosiphon stamineus. Subsequently, leaves (31.8%) and fruits (18.1%) were the most used plant parts for hypertension traditional treatments. The administration was mostly by oral ingestions, which were commonly eaten the raw or boiled plants or drinking decoction.